Реалізація моделі SQFD для забезпечення якості функціонування іт-сервісів - Заболотний, Є. О. (ХНУРЕ, 2024)
This paper presents the SQFD (Service Quality Function Deployment) model as an effective method for ensuring the quality of IT service functioning. SQFD helps organizations to identify user needs, translate them into technical characteristics, and develop services that meet these needs. This work explores the implementation of the SQFD model to enhance the quality of the language learning applications as a case study. Through SQFD, user requirements are prioritized, and translated into technical features. The model enables the assessment of user satisfaction, comparison with competitors, and evaluation of technical feasibility. This comprehensive approach facilitates informed decision making for product enhancement.
Keywords: функціонування іт-сервісів; реалізація моделі SQFD